TRIBOLOGY OF BIO-INSPIRED NANOWRINKLED FILMS ON ULTRASOFT SUBSTRATES - Juergen M. Lackner; Wolfgang Waldhauser; Lukasz Major; Christian Teichert; Paul Hartmann (Computational and Structural Biotechnology Journal, 2013)
Biomimetic design of new materials uses nature as antetype, learning from billions of years of evolution. This work emphasizes the mechanical and tribological properties of skin, combining both hardness and wear resistance of its surface (the stratum corneum) with high elasticity of the bulk (epidermis, dermis, hypodermis). The key for combination of such opposite properties is wrinkling, being consequence of intrinsic stresses in the bulk (soft tissue): Tribological contact to counterparts below the stress threshold for tissue trauma occurs on the thick hard stratum corneum layer pads, while tensile loads smooth out wrinkles in between these pads. Similar mechanism offers high tribological resistance to hard films on soft, flexible polymers, which is shown for diamond-like carbon (DLC) and titanium nitride thin films on ultrasoft polyurethane and harder polycarbonate substrates. The choice of these two compared substrate materials will show that ultra-soft substrate materials are decisive for the distinct tribological material. Hierarchical wrinkled structures of films on these substrates are due to high intrinsic compressive stress, which evolves during high energetic film growth. Incremental relaxation of these stresses occurs by compound deformation of film and elastic substrate surface, appearing in hierarchical nano-wrinkles. Nano-wrinkled topographies enable high elastic deformability of thin hard films, while overstressing results in zigzag film fracture along larger hierarchical wrinkle structures. Tribologically, these fracture mechanisms are highly important for ploughing and sliding of sharp and flat counterparts on hard-coated ultra-soft substrates like polyurethane. Concentration of polyurethane deformation under the applied normal loads occurs below these zigzag cracks. Unloading closes these cracks again. Even cyclic testing do not lead to film delamination and retain low friction behavior, if the adhesion to the substrate is high and the initial friction coefficient of the film against the sliding counterpart low, e.g. found for DLC.